Efficacy and Safety of Immunosuppressive Monotherapy Agents for IgA Nephropathy: A Network Meta-Analysis - Shisheng Han; Tianwen Yao; Yan Lu; Min Chen; Yanqiu Xu; Yi Wang (Frontiers Media S.A., 2021)
Background: The efficacy and safety of immunosuppressive monotherapy agents were evaluated for immunoglobulin A nephropathy (IgAN) using a network meta-analysis approach.Methods: Randomized controlled trials (RCTs) published prior to October 1, 2019, using immunosuppressive agents for treating IgAN, were systematically searched in PubMed, Embase, Cochrane Library, and Web of Science databases. Relative risks (RRs) or standard mean differences with 95% confidence intervals (CIs) were estimated using the random-effects model. The primary outcomes were clinical remission, end-stage renal disease (ESRD), and serious adverse events (SAEs). The secondary outcomes were urinary protein excretion and serum creatinine.Results: Twenty-five RCTs with 2,005 participants were deemed eligible. Six medications were evaluated: corticosteroids, mycophenolate mofetil (MMF), tacrolimus (TAC), cyclosporine, leflunomide, and hydroxychloroquine (HCQ). Steroids (RR 1.50, 95% CI 1.17-1.93), MMF (RR 2.05, 95% CI 1.15-3.65), TAC (RR 3.67, 95% CI 1.06-12.63), and HCQ (RR 3.25, 95% CI 1.05-10.09) significantly improved clinical remission rates compared to supportive care alone. Only steroids reduced the risk of ESRD (RR 0.35, 95% CI 0.12-0.98); however, there were significantly more SAEs than in the control group (RR 2.90, 95% CI 1.37-6.13). No significantly different effects in serum creatinine levels were found among the therapies. MMF showed no significant improvement in remission when excluding studies with a follow-up of fewer than 2 years in the sensitivity analysis (RR 1.41, 95% CI 0.40-4.92). The effect of TAC in the decrease of proteinuria was reversed after discontinuing medication for 3 months; the long-term effects of HCQ could not be evaluated due to the short follow-up duration.Conclusion: Corticosteroids might induce remission and increase renal survival in IgAN; however, adverse reactions should be taken into consideration. MMF, TAC, and HCQ might improve the remission of proteinuria when treating IgAN, but showed no superiority compared to steroids, and the long-term effects require further study.